Understanding How Gender Transformative Interventions Affect Adolescent Sexuality: A Cross-Cultural Perspective - Maddaleno-Herrera, M (Elsevier Inc., 2023)
Purpose: Early adolescence is a critical period for developing healthy sexual and reproductive health (SRH) knowledge, attitudes, and behaviors. However, a gap exists in interventions targeting very young adolescents that encompass the multilevel influences impacting healthy sexuality. This examination of two SRH programs in Indonesia and the Democratic Republic of Congo will elucidate facilitators and barriers to improving young adolescent sexuality. Methods: The Growing Up Great! (GUG) intervention in the Democratic Republic of Congo and Semangat Dunia Remaja or Teen Aspirations intervention in three districts in Indonesia were evaluated using the Global Early Adolescent Study survey. Adolescents were interviewed in 2017 and one year later in Kinshasa (n = 2,519). In Indonesia, baseline in 2018 was follow-up in 2020 in Bandar Lampung (n = 948), Denpasar (n = 1,156), and Semarang (n = 1,231). Outcomes included SRH knowledge and communication, awareness of SRH services, and attitudes about sexuality. Analysis followed a difference-in-difference approach to compare changes in each outcome over time between interventions and controls. Results: Both interventions improved pregnancy and HIV knowledge, while Semangat Dunia Remaja or Teen Aspirations also improved SRH communication. Results differed by site in Indonesia, with Semarang, the site that adhered most closely to intervention design, observed the most improvements. Differential effects were also seen by gender, especially in Kinshasa where girls advanced in SRH communication and knowledge but not boys. Girls in Semarang shifted normative SRH attitudes, and boys in Denpasar improved knowledge. Discussion: Interventions targeting very young adolescents can improve SRH knowledge, communication, and attitudes, though impact depends on context and implementation. Future programs should incorporate the community and environment influencing adolescent experiences with sexuality. © 2023